Professional Self-Determination Effect on the Content of Students Values in Pedagogical Institute - Babiy, Nikolai Fedorovich (Psychological Prospects Journal, 2012)
Professional self-determination is a selective approach to the world of professions in general and to the particular profession. Its kernel is the conscious choice of specialty, taking into account its own characteristics and capabilities, requirements of professional activities and socio-economic conditions. In a situation of strategic choices in vital (professional, educational) alternatives a person relies on the formed system of his values. Their contents may be different and vary depending on life priorities
Keywords: profession, professional self-determination, values, instrumental and terminal believes, goal-setting.